ENGLISH FOR ISLAMIC STUDIES IN INDONESIAN ESP CONTEXT - Rohmatun Hamidah, Wanda; Asmiyah, Siti; Yusuf, Arba'iyah (University of Darussalam Gontor, 2023)
This quantitative content analysis study explores the diversity of corpora in English for Islamic studies, focusing on three books from different Islamic universities: the State Islamic University of Sunan Ampel Surabaya (UINSA), University of Muhammadiyah Malang (UMM), and IAIN Walisongo. Using Antconc, the study analyzes the language and terminology used in these books. The findings reveal some diversities, including unique topics, different terms with similar meanings, and variations in word frequencies from the same word. The study has implications for ESP in Islamic Studies. It provides reference words for ESP practitioners teaching Islamic knowledge. The corpus can be published for learners interested in English words related to Islamic studies. It offers an overview of how these words are used.